PERBANDINGAN CERITA “SEMANGKA EMAS” DENGAN CERITA “BAWANG MERAH BAWANG PUTIH” - Binar Kurniasari Febrianti (tuahtalino, 2019)
This study aims to compare the intrinsic elements contained in the folklore of Semangka Emas and Bawang Merah Bawang Putih. By examining the comparison of the two folklores we can find out the similarities and differences that have different backgrounds and regions. The problem in this study is how the intrinsic elements in the two folklores and what are the similarities and differences of the two folklores. To solve problems and objectives in research applied qualitative descriptive methods. Data collection techniques by means of library study. The results of the study prove the folklore of the Semangka Emas and Bawang Putih Bawang Merah have similarities in theme, mandate, character, and plot. While the differences between the two folklore lies in the characterization and setting of the story. From the results of this study it can be concluded that both folklores have the similarity about jealousy towards siblings and the goodness of luck which is a reflection of social behavior, human relationships to others and other living creatures, as well as community norms.